Can Investment in Intangibles Explain the Swedish Productivity Boom in the 1990s? - Harald Edquist (Research Institute of Industrial Economics (IFN), 2009)
After a severe crisis in the early 1990s, the Swedish economy experienced a boom in productivity growth. According to economists there have been primarily three explanations for the fast productivity growth in 19952004: Market reforms, recovery from the crisis and the impact of information and communication technology (ICT). This paper offers an alternative view by recognizing that firms make substantial investment in intangible assets such as R&D, design, advertising etc. These investments are not classified as investment in the National Accounts, where only tangible assets are defined as investment. This paper provides estimates of investment in intangible assets and uses the growth accounting framework to analyze the Swedish productivity boom. The results show that investment in intangibles was approximately 246 bn SEK in 2004 or 9 percent of GDP. Moreover, intangible capital accounted for almost 50 percent of labor productivity growth in the Swedish business sector 19952004. Thus, investment in intangibles was an important source to the Swedish productivity boom in 19952004.
Keywords: O15; O16; O47; O52; 330; Intangibles; Investment; Economic growth; Immaterielle Werte; Investition; Wirtschaftswachstum; Arbeitsproduktivität; Schweden